Stakes is high : life after the American dream - Smith, Mychal Denzel, 1986- (Bold Type Books, 2020)
"We are better than this" has been the rallying cry since Donald Trump was elected. But as New York Times-bestselling author Mychal Denzel Smith shows, Americans are too comfortable imagining our greatness. We like to believe in the rightness of our path and the inevitability of choosing our better angels. But historically, we've only come close to living up to the ideals we profess after we've been dragged, kicking and screaming, toward justice. Growth only happens when we confront our deceptions and our own complicity in them. In Stakes Is High, Smith exposes the contradictions at the heart of American life - between patriotism and justice, between freedom and inequality, incarceration, police violence. In a series of incisive essays, Smith holds us to account individually and as a nation. He examines his own shortcomings, grapples with the anxiety of feeling stuck, and looks in new directions for the tools to build a just America. He questions whether Martin Luther King, Jr. can ever really be the hero we need in our time, untangles the persistent cultural power of Bill Cosby, and weighs the value of police and prison abolition. Stakes Is High establishes Mychal Denzel Smith as a voice to be heeded as we prepare for the fight ahead"--